To use the elimination method to solve a system of equations, one of the equations is multiplied by a constant so that when the two equations are added or subtracted, one of the variables will cancel out.

For example, consider the following system of equations:

3x + 2y = 12

4x - 3y = 5

One way to eliminate the y variable is to multiply the first equation by -3 and add it to the second equation:

(3x + 2y = 12) * -3 + (4x - 3y = 5)

-9x - 6y = -36 + 4x - 3y = 5

-5x = -31

x = 6

Now that we have x = 6, we can substitute this back into one of the original equations to find y

3x + 2y = 12

3(6) + 2y = 12

18 + 2y = 12

2y = -6

y = -3

So the solution of the system of equations is x = 6

## Teaching a system of equations by elimination Easily

- Using real-world examples: Provide students with real-world examples of situations that involve systems of equations, such as in physics, engineering or economics. This can help students understand the concept and apply it to new situations.
- Guided practice: Provide students with guided worksheets that involve solving a system of equations using the elimination method. Start with simple examples and gradually increase the difficulty level.

Show all